L’injonction thérapeutique à l’égard des toxicomanes : comparaison des systèmes français et québécois - Facy, François; Brochu, Serge; Simon, Françoise (Criminologie, 1996)
In Canada, the total amount of accusations, in compliance with the laws on drugs, show a slight but constant progression. More than half of the sentences for drug-linked offenses have lead to incarceration, a third of the people sentenced for a simple drug possession have been jailed. The relevance of these sentences, making the Canadian detention centres populated with more drug addicts than the rehabilitation centres, is questionable.In France, legislation is mostly based on the December 31st, 1970 law: drug use and trafficking are severely punished. However, for a first arrest, the prosecutor can enjoin the arrestee to treatment: this is what is called therapeutic injunction. Even though therapeutic injunction spares substance users from a jail term, some limitations are encountered this measure is selective, based on social and judicial criteria, making it more forgiving than the average characteristics of drug addicts, it is only accepted and applied by half of the subjects. A specific inquiry has been done in a department in the Paris region, where drug addiction activity is abundant, and suggested a preventive role for the injunction in cases of recidivism. Global appreciation of the therapeutic injunction remains nuanced in a context of new measures in drug addiction, but it translates into the increasing necessity to introduce professional networks between the judicial and sanitary systems, intended for a young population dealing with the modern difficulties of social adaptation and high risk behaviour.